Assessing health-related quality of life outcomes after the surgical removal of a mandibular third molar - Gabrić, Dragana; Brozović, Juraj, stomatolog; Sušić, Mato; Katanec, Davor; Bego, Krešimir; Kobler, Pavel (2009)
Abstract: ality of life (HRQoL) in the postoperative period. Data was obtained from 101 patients who had undergone 105 surgical procedures. Only one mandibular third molar was removed per visit. The inclusion criterion for surgical procedures was creating a mucoperiosteal flap either with or without osteotomy. Surgical details were noted in a pre-made questionnaire. A self-administered health-related quality of life questionnaire, designed for assessment of the patient’s perception of recovery for pain, lifestyle and oral function, was given to all patients. Patients evaluated postoperative pain and other sequelae on a scale ranging from 0 (none) to 3 (severe). Follow-up visits were scheduled on the third and the seventh postoperative day, when wound healing was clinically evaluated and noted. At the review appointment, one week later, patients had their sutures removed and returned a completed follow-up questionnaire. Patients were contacted 14 days after surgery for the purpose of gathering additional data pertaining to their recovery. The mean score for pain had a peak value on day one (1.8), and showed an exponential decrease (1.2 on day three, 0.5 on day seven, 0.1 on day 14). All the other postoperative sequelae showed the same tendency to decrease exponentially. The type of operative procedure and tooth position showed significant impact on postoperative recovery. The surgical removal of a mandibular third molar causes severe deterioration in a patient’s quality of life during the first 3 days postoperatively. The quality of life can be expected to return to a preoperative level by the end of the first postoperative week
Bibliografija: 30 jed
Sažetak
Keywords: Kvaliteta života -- Kirurško uklanjanje -- Donji treći molar